60 $$^{° }$$ Flat PWM technique for single-source switched-capacitor multilevel inverter with quadruple voltage boost and enhanced output - Oorappan G. M; Lakshmanan S. A; Jagabar Sathik M (Scientific Reports)
Abstract This paper introduces a new 60 $$^{° }$$ Flat PWM Technique for Single-Source Switched-Capacitor(SC) Multilevel Inverter with Quadruple Boost (60FP-MLI-QB) and Enhanced Output. The proposed design generates nine output levels with lower switching losses using the 60 $$^{° }$$ Flat PWM (60FP) Technique. Furthermore, this technique increases the voltage gain enhancement while flattening the sine wave at its peak. The driven inverter topology includes 11 switches, two capacitors, and a diode, with each levels circuit connected through six or five switches. The performance of the proposed 60FP-MLI-QB is tested through simulation and hardware experiments under various dynamic conditions, showing its flexibility and superiority compared to similar configurations. Moreover, the paper presents a harmonic minimization technique through various FP methods by modifying the sinusoidal modulation reference.